PENINGKATAN KUALITAS HIDUP LANSIA â€˜â€™PERSONAL HYGIENE DAN PENYAKIT DEGENERATIF PADA LANSIAâ€ DI DESA SUGIHREJO, KECAMATAN KAWEDANAN, KABUPATEN MAGETAN - Ramadhanintyas, Karina Nur; Marsanti, Avicena Sakufa (Universitas Respati Yogyakarta, 2021)
Personal hygiene is a basic requirement that includes skin care, bathing, oral care, eye care, nose, ears, hair care, and foot and nail care. The need for personal hygiene should be a top priority for the elderly because with good personal hygiene makes the elderly have a low risk of developing infectious diseases, in the eyes and ears. As for the description of personal hygiene behavior of the elderly that must be met, which is a basic need that includes skin care, bathing, oral care, eye care, nose, ears, hair care, as well as foot and nailcare. Personal hygiene must always be fulfilled in the arena is a specific primary preventive measure to minimize bacterial microorganisms that ultimately prevent a person from getting disease Personal hygiene needs should be a top priority for the elderly because with good personal hygiene makes the elderly have a low risk of developing infectious diseases, in the eyes and ears.Â Keywords: Â quality of life, elderly, personal hygiene